SUPERVISI MANAJERIAL DAN PERAN SUPERVISOR DALAM PENINGKATAN KUALITAS AKADEMIK DAN KELEMBAGAAN PENDIDIKAN ISLAM - Akmal Ahmad (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2022)
Abstract: Managerial supervision is very important in organizations because they drive the entire school program, from leadership, curriculum, student affairs, infrastructure, budget, and public relations. The purpose of this study is to analyze and understand managerial and supervisory supervision, the components of supervision activities, academic quality improvement and institutional quality improvement. The method used in this research is the library research approach. Literature study is a study that is used to collect information and data with the help of various materials in the library. And the results of this study are that in the process of implementing the Quality Improvement of Academic and Institutional Islamic Education, managerial supervisors must really understand the components of activities in supervision by planning a supervision program, implementing a supervision program, and following up on the results of the implementation of supervision later to improve quality. and institutional quality begins with carrying out maximum supervision activities by paying attention to 3 things, namely careful planning, maximum implementation, and immediate follow-up of supervision activities.